Study of friction and wear behaviors of Fe-based amorphous coatings by MD simulations - Chu, Zhenhua; Zhou, Yuyun; Xu, Fa; Xu, Jingxiang; Zheng, Xingwei; Luo, Xiaotao; Shu, Yan; Zhang, Zheng; Hu, Qingsong (Frontiers in Materials, 2022)
In this work, Molecular Dynamics simulation is adopted to investigate the friction and wear mechanism of Fe-based amorphous composited coatings. It is found that the ceramic phase can improve plasticity of the composite coatings to reduce wear. And when the Al2O3 content is 15 wt.%, due to the stress concentration between ceramic phase and amorphous phase, the viscosity flow in the amorphous phase results in the plastic deformation. So the best wear resistance was obtained. In addition, with the increase of compression depth, the number of atoms accumulated is more and more increasing, and the degree of plastic deformation is getting deeper in the composite coatings. For the sliding speed, high sliding speed results in the reduce of the wear resistance of coatings.